Increased vertebral canal diameter measured by ultrasonography as a sign of vasculitis in patients with giant cell arteritis - Ayo-Martin, Oscar; Garcia-Garcia, Jorge; Hernandez-Fernandez, Francisco; Palao, Maria; Poyatos-Herraiz, Beatriz; Barahona-Espinal, Tito Humberto; Gonzalez-Romero, Alberto; Marin-Conesa, Ester; Serrano-Serrano, Blanca; Paya, Maria; Segura, Tomas (Frontiers in Medicine, 2023)
The diagnosis of giant cell arteritis (GCA) by ultrasonography including large vessels, apart from the temporal artery increases the sensibility of the study and informs about the risk of specific complications. However, there is less information about the study of these arteries, whose affection carries higher proportion of severe complications.To describe and analyze the value of the diameter of the cervical vertebral canal of the vertebral artery (VA) as a sign of vertebral vasculitis (VV) related to GCA and estimate the risk of stroke complications.Observational study of a population that includes patients with GCA with and without VA vasculitis as well as healthy subjects. We evaluated whether there were differences in VA diameter in the groups and, if so, we estimated the diagnostic capacity of the variable that best defines VA diameter using a ROC curve. Cut-off points with their associated reliability chosen thereafter.There were 347 subjects included:107 with GCA of whom 37 had vertebral vasculitis, 240 healthy controls. In patients with GCA and VV, the VA diameter was increased (No GCA 3.4 mm, GCA without VV 3.6mm, GCA with VV 5.2mm p<0'01).According to the ROC curves, the variable defining vertebral diameter with best diagnostic accuracy is the sum of both sides (area under the curve of 0.98). With a cut-off point of 8.45 mm, the reliability values are: sensitivity 94.1%, specificity 94.5%, PPV 82.1% and NPV 98.4%. With a cutoff point of 9.95 mm, the sensitivity is 52.9% and the specificity is 100%. Likewise, VA diameter is independently associated with the presence of stroke in the vertebrobasilar territory (OR 1.6, range 1.2-2.2).The VA diameter, measured as the sum of both sides, is an objectively measurable sign with very high reliability for detect vertebral vasculitis in patients with GCA. It is proposed here as a novel echographic sign, which can aid the detection of the involvement of an artery where the complications are especially serious.